Validating a bike network analysis score based on open data as a connectivity measure of urban cycling infrastructure adapted for European Cities - Abad Crespo, Lorena Cristina (2019)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies